The importance of shift work: the hospitality sector - Martins, Dora (2021)
This study explores the importance of shift work in the organizational context of the hospitality sector. To answer its four research objectives: (1) to identify the degree of satisfaction with the shift work regime; (2) to characterize individual motivations for doing shift work; (3) to understand the impact of shift work on the worker’s physical, mental, social well-being and family environment and (4) to identify the willingness for choosing shift work a survey was developed, published online and it gathered the answers of 153 shift workers in the hospitality sector. The results indicate that the main motivation to work in shifts is related to the requirement of the function itself. The degree of satisfaction of workers doing shift work tends to decrease when they evaluate their satisfaction with the balance between work life and the other dimensions - personal, family, and social life. Most respondents say that if they could choose, they would not work in shifts, considering its negative effects on their physical and mental wellbeing, as well as on their family and social well-being. From the results obtained, we will contribute to the literature on shift work by showing the need for greater organizational support, be it at the level of physical conditions of work or the level of benefits promoting social well-being for this category of workers.